Origin of the Pd-Rich Pentlandite in the Massive Sulfide Ores of the Talnakh Deposit, Norilsk Region, Russia - Valery Kalugin; Viktor Gusev; Nadezhda Tolstykh; Andrey Lavrenchuk; Elena Nigmatulina (Minerals, 2021)
Pd-rich pentlandite (PdPn) along with ore-forming pentlandite (Pn) occurs in the cubanite and chalcopyrite massive sulfide ores in the EM-7 well of the Southern-2 ore body of the Talnakh deposit. PdPn forms groups of small grains and comprises marginal areas in large crystals of Pn. The palladium content in PdPn reaches up to 11.26 wt.%. EDS elemental mapping and a contour map of palladium concentrations indicate distinct variations in the palladium content within and between individual grains. Palladium distribution in the large grains is uneven and non-zoned. PdPn was formed as the result of a superimposed process, which is not associated with either the sulfide liquid crystallization or the subsolidus transformations of sulfides. Deming regression calculations demonstrated the isomorphic substitution character of Ni by 0.71 Pd and 0.30 Fe (apfu), leading to PdPn occurrence. The replacement of Ni by Fe may also indicate a change in sulfur fugacity, compared to that taking place during the crystallization of the primary Pn. The transformation of Pn into PdPn could have occurred under the influence of a Pd-bearing fluid, which separated from the crystallizing body of the massive sulfide ores.